Symptoms of Spanish Fantasies: Africa as the Sign of the Other in Angel Ganivet's Idearium español and La conquista del reino de Maya - Yaw Agawu-Kakraba (Studies in 20th & 21st Century Literature, 2006)
Angel Ganivet's La conquista del reino de Maya (1897, The Conquest of the Realm of Maya) elucidates the aggressive impulse embedded within modern self-consciousness, one that precipitates the need for journeys—linguistic and artistic, as well as authentically colonial—to either the "dark continent" or to the "heart of darkness" to find the irrational Other of the rational modern man. This impulse, however, is not only at the service of individual subjective experience, elevating the ego in relation to a declining awareness of objective or synchronous outside reality. That modernity also precipitated the creation of modern nations, often in conjunction with imperial enterprises, which mark the individual as a particularly national subject. Thus, in order to understand more fully the irony of Ganivet's strategies in his novel, I first explore how he articulates the self and the nation's identity within the parameters of a modernist discourse in his Idearium español (1897, Ideas of Spain), since he locates that self within the contrasting view of the Other in La conquista. The embedded contradiction lies in a rhetoric that seeks to defend territorial integrity and, at the same time, subjugate the African subject outside that territory.
Keywords: Angel Ganivet; La conquista del reino en Maya; the conquest of the realm of the Maya; self-consciousness; journey; colonialism; other; rational; irrational; reality; la conquista; Africa; African; territory; idearium español